Sistem Pendukung Keputusan Penerima Bantuan Sosial Menggunakan Metode Multi-Factor Evaluation Process (MFEP) pada Dinas Sosial Tanjungpinang - Hendi Setiawan; Tommy Darian (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2023)
This research was compiled based on the results of the analysis of the current system and the results of the system design carried out at the Tanjungpinang City Social Service. The results of the analysis show that the data processing for selecting recipients of Uninhabitable Houses (RS-RTLH) for incoming mail still uses a manual system, that is, it has not used a system so that it takes a relatively longer time and is less efficient when making decisions. To correct the ongoing shortcomings, a new system designed to increase efficiency and effectiveness in assisting assessments can help design a grant program to assist social service employees to create a decision support system for the selection of beneficiaries using the MFEP method. This application is built using Visual Basic programming language and MySQL database, the methodology used is the waterfall method. With the existence of this new system and application, it is expected to increase the efficiency of the existing performance in the agency.